Can the common-factor hypothesis explain the observed housing wealth effect? - Narayan Bulusu; Jefferson Duarte; Carles Vergara-Alert (Bank of Canada, 2016)
The common-factor hypothesis is one possible explanation for the housing wealth effect. Under this hypothesis, house price appreciation is related to changes in consumption as long as the available proxies for the common driver of housing and non-housing demand are noisy and housing supply is not perfectly elastic. We simulate a model in which a common factor drives the relation between house prices and consumption to examine the extent to which the common-factor hypothesis can explain the housing wealth effect. Our results indicate that the common-factor hypothesis can easily explain the strong housing wealth effect estimated with US state-level data.
Keywords: E21; R31; 330; Economic models; Housing